Analisis Peran Guru Dalam Memfasilitasi Peserta Didik Pada Keikutsertaan OSN Bidang Matematika - Deri Wahyu Iskandar; Riza Fatimah Zahrah; Geri Syahril Sidik (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
When there was an OSN competition in mathematics at SDN Kotabaru several times entered the top 3 at the sub-district level, because of that the role of teachers became very important in guiding students in developing their potential to obtain the achievements made by these students. The purpose of this study is to find out how teachers find potential interests in students' talents and how teachers guide students to OSN in mathematics. The subject used was one student who had attended OSN in mathematics the previous year and his supervisor. The method used in this study is qualitative descriptive. Data collection techniques use observation, interviews and documentation. Based on the results of research, the role of teachers is very important in developing the potential of students, but before developing it, teachers need to know in advance what potential exists in students. According to Desmita, categorizing potential into two, namely physical potential in the form of physical ability and endurance such as sports, dance, martial arts and so on. The second potential is in the form of psychological potential that can be categorized into multiple intelligences.